Cuidados e descuidos na atenção a desatentos : reflexões a partir da clínica psicopedagógica - Andrade, Maria Alice Castello de (2014)
This study derives from a broad psychopedagogical clinical practice along with the supposed unfocused some diagnosed with ADHD, many pre-diagnosed by their own schools which was imposed driven by repeated evidences, that already in the first sessions demonstrate preserved ability to remain focused; that past and/or current environmental flaws stand out in their life journeys; that in face of a therapeutic process committed to the simultaneous attention to these individuals and the outside reality around them, many (re)assume the educational path autonomously. The research goes back to the general assumption that the lack of attention to the real conditions and needs of these children is related to the cause and/or the maintenance of the clinical condition of inattention, which remotes to the different instances of caring parents, school, doctors, psychopedagogues, etc. in order to instigate reflections around the quality of shared caring and eventual repositioning. The investigative course begins with reference to the contemporary problematic of proliferation and trivialization of the ADHD diagnosis the different ways of comprehending a clinical condition, the debating and controversy, the involved sociocultural factors followed by clarifications related to the psychopedagogy field, its elements and contributions to the reflection in question. The General Caring Theory by Luís Claudio Figueiredo is then evoked as a guiding axis to the discussion around the clinical findings of the unfocused upon presentation and analysis of an exemplifying clinical case from which it is intended not only to point out the relevance of discriminating unhealthy aspects of caring throughout the life path of the supposed unfocused, but also to highlight the factors which stipulate conditions for the required ethical caring, so that it can be (re)established by coordinately confronting the problematic